Accounting in the Addressing of Economic and Social Needs in Terms of Sustainable Development. Experience from Training Projects in the Health Care System - Baran, Wioletta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: To examine the impact of accounting on economic and social needs, including the management needs of medical entities terms seeking sustainable development, on the example of training and research projects.Research Design & Methods: Accounting is described from the perspective of sustainable development, thanks to the information, educational and application capabilities of this system. Participatory observation, critical analysis and synthesis are used.Findings: Monitored and controlled activities in training and research projects were adjusted to the needs of healthcare entities, making it possible to achieve the anticipated impact on the economic and social environment. The accounting system is shown to be flexible, and thus it is used in the creation of decision-making bases for actions taken for sustainable development.Implications / Recommendations: The use of feedback activity appropriate for the operation of information systems, including the accounting system under consideration, makes educational and application possibilities of accounting a real response to the growing economic and social needs of stakeholders. Education in accounting falls within the category of high-quality education – that is, education that combines knowledge and skills and flexibly responds to economic and social needs, including the management needs of healthcare entities.Contribution: The use of universal features of the accounting system, but above all its informational, educational, and application capabilities in response to correctly identified economic and social needs of various types, including types of entities, will determine the shape of an effective accounting system. Effectiveness will mean it is successfully used in the preparation of applicable information for making all kinds of decisions, including those that contribute to sustainable development.